Performance Improvement Strategy of Supply Chain Management in SEI Galuh Palm Oil Mill, PT Perkebunan Nusantara V - Ifri Handi Lubis; Taufik Djatna; Tanti Novianti (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Palm oil becomes Indonesia's leading agricultural commodity which is inseparable from competition with CPO producers from other countries. PT Perkebunan Nusantara V (PTPN-V) is a state-owned company engaged in palm oil plantation and processing palm oil fresh fruit into crude palm oil (CPO) and palm kernel (palm kernel). One of the 12 palm oil processing units of PTPN-V is the Sei Galuh Palm Oil Mill (PKS SGH), in the past 5 years the plant has the lowest performance compared to 12 other factories. Therefore, the purpose of this research is to analyze the supply chain of PKS SGH and performance improvement strategy of supply chain management at the PKS SGH through SCOR-AHP approach. The result shows that supply chain strategy in this research is to run lean supply chain strategy because the output is a functional product. So the strategy applied was should low cost strategy (efficient). The result of performance measurements obtained matrix order fulfillment, quality conformity, processing cycle time, and employee costs is “good”. Then, matrix order fulfillment time, flexibility of capacity increase and cash to cash cycle is “average”; while matrix supply flexibility and cost of processing were obtained “poor” results.Keywords: supply chain, SCOR, AHP, crude palm oil (CPO), PTPN-V